2016
DOI: 10.1007/s11606-016-3643-0
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Variation in Antibiotic Prescribing for Acute Respiratory Infections?

Abstract: BACKGROUND: Acute respiratory infections are the most common symptomatic reason for seeking care among patients in the US, and account for the majority of all antibiotic prescribing, yet a large fraction of antibiotic prescriptions are inappropriate. OBJECTIVE: We sought to identify the underlying factors driving variation in antibiotic prescribing across clinicians and settings. DESIGN, PARTICIPANTS: Using electronic health data for adult ambulatory visits for acute respiratory infections to a retail clinic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…For example, when controlling for patient characteristics, the odds of receiving an antibiotic prescription were approximately 10 times higher for patients who visited Clinic D compared with those who visited Clinic A. We considered whether encounter volume and time pressure within a clinic might influence prescribing decisions [26]; however, provider workload was not correlated with the decision to prescribe an antibiotic. Studies have noted that cultural factors (such as patient attitudes) and other external forces (such as insurance type, accessibility and price of antibiotics, or public opinion) may influence the prescribing of antibiotics [7, 26–29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, when controlling for patient characteristics, the odds of receiving an antibiotic prescription were approximately 10 times higher for patients who visited Clinic D compared with those who visited Clinic A. We considered whether encounter volume and time pressure within a clinic might influence prescribing decisions [26]; however, provider workload was not correlated with the decision to prescribe an antibiotic. Studies have noted that cultural factors (such as patient attitudes) and other external forces (such as insurance type, accessibility and price of antibiotics, or public opinion) may influence the prescribing of antibiotics [7, 26–29].…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not assess the differences between high and low prescribers regarding these issues. Prior surveys, [15][16][17] which were not based on qualitative interviews, also did not consider the prescribing rates of the respondents. One study of emergency physicians found that high prescribers tended to see antibiotic prescribing as an opportunity to shorten infection at no cost, whereas low prescribers appreciated the potential harms of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Questions relating to clinical factors that might influence antibiotic prescribing were based on existing guidelines for antibiotics. 2,14 Based on prior studies, [15][16][17] we included questions that addressed nonclinical factors such as patients requesting antibiotics, concern for patient satisfaction, and time pressure. We also included questions probing selfreflection of prescribing patterns relative to their peers because interventions that provide physician with audit and feedback 6 have been shown to decrease inappropriate prescribing.…”
Section: Qualitative Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also validate previous reports on antibiotic use in Australian general practice, demonstrating a heavy reliance on broad‐spectrum antibiotics, seasonal variations in prescribing and reduction in the frequency of cefaclor and roxithromycin prescribing . Descriptions of broad‐spectrum antibiotic use, winter peaks in prescribing and inter‐practice variation are also reported in the international literature.…”
Section: Discussionmentioning
confidence: 99%